Laclede, Pottawatomie County - Cook, Aubrey (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study describes the unique evolution of the small community of Laclede in Pottawatomie County, Kansas. Laclede transformed from a failed town to a preserved historical community owned by a single family. The study includes a personal interview, fieldwork, maps and photographs.
Aubrey Cook, “Laclede, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/83.
Keywords: Belvue; Center Township; Pottawatomie County; Onaga Road; Tannerville School; Highway 24